Development of Zakat Distribution in the Disturbance Era - Mu’adil Faizin; Suud Sarim Karimullah; Bhismoadi Tri Wahyu Faizal; Ihsan Helmi Lubis (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
With the growing number of publications on digital zakat, there is a pressing need for research on zakat management to develop general concepts that can serve as policy standards for zakat management practitioners and national zakat regulators. This research aims to provide insights into managing zakat in an easy, flexible, transparent, and targeted manner. The study employs field research methods, observing real events in society, and uses empirical legal research techniques with an interdisciplinary approach, incorporating sociological and ethnographic studies. The findings indicate that proper zakat distribution requires a deep understanding of its fiqh, grounded in shari'a texts and explored through both a linguistic approach (al-qowâid al-lughawiyyah) and an objective shari'a approach (maqâshid asy-syarî'ah). Furthermore, collecting zakat funds by national amil zakat agencies and institutions in Indonesia must adapt to contemporary times and technology, providing an alternative that facilitates muzakkī's in fulfilling their obligations